2009
DOI: 10.1111/j.1399-0012.2008.00934.x
|View full text |Cite
|
Sign up to set email alerts
|

Tacrolimus in pediatric heart transplantation: ameliorated side effects in the steroid‐free, statin era

Abstract: Due to concerns over the side effects of cyclosporine, tacrolimus is widely used in pediatric heart transplantation. However, tacrolimus therapy is also accompanied by potentially serious side effects. This paper examines the side effect profile of tacrolimus in a large group of pediatric heart recipients. Data on renal function, diabetes, hyperlipidemia and hypertension were collected by case-note review of 100 patients who had received . OR = 12 months treatment with tacrolimus. Forty-two patients received t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…The effect of immunosuppression as a therapy for SCI could be explained by these observations. Tacrolimus (also called FK506), a kind of macrolides immune inhibitor, is widely used in organ transplantation (Fukudo et al 2009;Simmonds et al 2009). It can promote physiological functional recovery of transplanted allogeneic limbs (Dubernard et al 2003), and improve the locomotor function of limbs after SCI (Madsen et al 1998;Voda et al 2005;Pan et al 2006a) In the present study, it was also found that tacrolimus effected statistically significant improvements after SCI, as quantified by the BBB score, the inclined plane test, footprint analysis, electrophysiological tests and electron microscopic analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of immunosuppression as a therapy for SCI could be explained by these observations. Tacrolimus (also called FK506), a kind of macrolides immune inhibitor, is widely used in organ transplantation (Fukudo et al 2009;Simmonds et al 2009). It can promote physiological functional recovery of transplanted allogeneic limbs (Dubernard et al 2003), and improve the locomotor function of limbs after SCI (Madsen et al 1998;Voda et al 2005;Pan et al 2006a) In the present study, it was also found that tacrolimus effected statistically significant improvements after SCI, as quantified by the BBB score, the inclined plane test, footprint analysis, electrophysiological tests and electron microscopic analysis.…”
Section: Discussionmentioning
confidence: 99%
“…After removing all duplicates and papers not meeting the inclusion criteria, eighteen papers were considered relevant. Twelve papers reported on liver, one on combined heart and lung transplant , four on heart transplant , and one on intestinal transplant recipients (Fig. ) .…”
Section: Resultsmentioning
confidence: 99%
“…We identified five papers reporting on renal function after transplantation in either heart and lung transplant recipients or heart transplant recipients published between 1999 and 2011 (Table ). Ages ranged from seven hours until 18 yr. Four papers used the age‐ and gender‐adjusted Schwartz formula to calculate the GFR; one of these used a cutoff criterion to determine CKD . The prevalence of CKD in these papers ranged from 6.8% to 46% with a follow‐up time ranging from 14 days post‐transplantation to seven yr post‐transplantation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tacrolimus is now the most commonly used CNI in pediatric heart transplantation in North America. Conversion from cyclosporine to tacrolimus may be helpful to ameliorate specific side effects, such as hirsutism and gingival hyperplasia [11,29].…”
Section: Tacrolimusmentioning
confidence: 99%